Characterization of the clinical-epidemiological and physiological management of patients with clinical profile acute edema (Research, Society and Development, 2022)
Acute Lung Edema (APE) is one of the main cardiopulmonary complications that require physical therapy care in emergency departments. Thus, this study aims to describe the clinical and epidemiological profile of patients with APE admitted to a public hospital and to identify the physical therapy approaches used in the management of such individuals. This is a descriptive study with a quantitative approach, carried out from the medical records of a public hospital, from May 2018 to May 2019. The data collected were submitted to the analysis of simple descriptive statistics, through calculations of the means and standard deviation for the quantitative variables, and the presentation of the absolute and relative frequencies for the categorical variables. Ninety records were found, with a homogeneous frequency between the sexes, with no predominance between them, most patients were elderly, had passed through the emergency room, had cardiogenic PAE, with associated cardiac pathologies, hypertensive and diabetic patients. Hospital discharge was the most frequent outcome. It was evidenced that cardiorespiratory monitoring, kinesiotherapy and Non-Invasive Mechanical Ventilation are the main approaches of the therapeutic plan and kinesiotherapy, cardiorespiratory monitoring and oxygen therapy are the most performed conducts by physical therapists.